The Effect of Giving Dates Extract (phoenix dectylifera) on Maternity Mothers on the Progress of Childbirth - St. Surya Indah Nurdin; Siskawati Umar (PSPP JOURNALS, 2021)
Progress of labor when the first phase is active is when the exhausting, and very severe where most seoarang mother will begin to feel pain or pain that getting old is getting increased, the phase of this activity of the uterus begin to more actively and Mom would start exhaustion so very me m need nutritional intake so that mothers can still get energy . The aim of the research is to find out Effect of Giving Sari Kurma ( Phoenix Dectylifera ) On Mother Maternity Against the Advancement of Labor . The method that is used the study of literature or literature review. The results of the research of this is there Effect of Giving Sari Kurma ( Phoenix Dectylifera ) On Mother Maternity Against the Advancement of Labor.